Paris 2024 - Averbuck, Alexis, 1972-; Fong Yan, Fabienne; Rothery, Madeleine; Stewart, Nicola Leigh; Carillet, Jean-Bernard; Hossenally, Rooksana (Lonely Planet guidebooks., 2024)
"Lonely Planet's Paris is our most comprehensive guide that extensively covers all the city has to offer, with recommendations for both popular and lesser-known experiences. Admire masterpieces in the Louvre, sample French cuisine and window shop down boulevards; all with your trusted travel companion"--